The dependence of yield and quality indicators of seeds of millet, depending on the time and method of sowing - Полторецький, С. П.; Полторецька, Н. М. (Scientific Progress & Innovations, 2015)
The result of researches with the application of method of correlation pleiads of the influence of different terms and methods of sowing on sowing qualities and crop capacity of the seeds of millet broomcorn under conditions of unsustainable moisturizing of the southern part of Right-Bank Forest-Steppe zone were analyzed.